Chilly Autumn Evenings (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
Chilly Autumn Evenings is a suspenseful tale that operates on two different planes of time: the 1960s and the 2010s. Composed in a fiction composition workshop, the piece seeks to address themes of family, generational entanglement, and the persistence of memory and hurt. For additional context, listen to the author's reflection on the piece below.